2007
DOI: 10.1007/s10540-007-9053-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nickel on Human and Fish Red Blood Cells

Abstract: The objective of this study was to assess the effects of nickel chloride on human and rainbow trout erythrocytes in vitro. The cells were incubated with 0, 0.5 and 1 mM nickel chloride for 1 h at pH 7.40 and 25 degrees C, then K(+) efflux, SO (4) (2-) uptake and GSH and GSSG concentrations were measured. In both kind of cells, "high concentration" nickel treatment increased KCl efflux with respect to the control. The SO (4) (2-) uptake was not significantly different at "low nickel concentration" but was lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Sulphate influx measured in Liza aurata and Salmo irideus erythrocytes. 34 These data support the use of kinetics of flux measured in the fish RBCs to assess the activity of anion exchange operating from band 3, which appears in marked manner in RBCs of L. aurata and S. irideus. Bars represent mean AE SD in percentage for temperature, pH and dissolved oxygen (which ranged between 10.97% and 33.33%) and significant changes in percentage for salinity (100%).…”
Section: Discussionsupporting
confidence: 73%
“…Sulphate influx measured in Liza aurata and Salmo irideus erythrocytes. 34 These data support the use of kinetics of flux measured in the fish RBCs to assess the activity of anion exchange operating from band 3, which appears in marked manner in RBCs of L. aurata and S. irideus. Bars represent mean AE SD in percentage for temperature, pH and dissolved oxygen (which ranged between 10.97% and 33.33%) and significant changes in percentage for salinity (100%).…”
Section: Discussionsupporting
confidence: 73%
“…In the late exposure period, the exposed GSH/ GSSG ratio was significantly different from the control, which might highlight that Ni exerts toxicity on the treated copepods via alteration of the cellular redox state. Similarly, some authors attribute the toxic effects of Ni to a decrease in cellular GSH and a concomitant increase in GSSG, altering the redox state of the cells (De Luca et al 2007). Thus, GSH/GSSG could be a suitable biomarker for oxidative stress or injury in biological organisms (Hwang et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its position, the protein is continuously damaged by chemical agents and drugs circulating in the blood. Previous studies reported that some metals enhance the degradation of band 3 protein after it has been treated with chemical substances likely to affect sulphate permeability and modulate anion influx through the erythrocyte membranes [22]. Oxidation, caused by high concentrations of lead chloride, changed the -SH groups into SS-groups, resulting in a conformational change in the protein structure.…”
Section: Discussionmentioning
confidence: 99%